(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Eclampsia, a life threatening complication of pregnancy. It is one of the important cause of maternal mortality of Bangladesh. Eclamptic seizure can effectively controlled by use of magnesium sulphate. A prospective randomized case control study was conducted at eclampsia ward of Dhaka Medical College Hospital for one year from June 2007 to May 2008. Objective: To find out whether only 8gm of magnesium sulphate heptahydrate (Nalepsin) as a single loading dose is sufficient to control eclamptic convulsion and also to compare the efficacy between 8gm & 10gm of MgSo4 used to control convulsion. Methodology: A random selection was done by lottery of those antepartum and intrapartum cases who fulfill the selection criteria. Hundred patient were selected and grouped them into case & control. 8gm Nalepsion (Magnesium sulphate heptahydrate) as a single I.V dose was selected for case and 10gm MgSo4 (4gm I.V + 3gm I.M in each buttock) was for control group. Different variables were compaired and results were analyzed by unpaired t test and chi-square test (X2) by SPSS programme. Result: Statistically there was no significant difference of any finding between two groups after comparing all variables individually. Conclusion: 8gm Nalepsin intravenously as a single loading dose is sufficient to control eclamptic convulsion and prevention of its recurrence. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13743 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 71-76